Shift in Bacterial Community Structure Drives Different Atrazine-Degrading Efficiencies - Liu, Xiaowei; Chen, Kai; Chuang, Shaochuang; Xu, Xihui; Jiang, Jiandong (Frontiers in Microbiology, 2019)
Compositions of pollutant-catabolic consortia and interactions between community members greatly affect the efficiency of pollutant catabolism. However, the relationships between community structure and efficiency of catabolic function in pollutant-catabolic consortia remain largely unknown. In this study, an original enrichment (AT) capable of degrading atrazine was obtained. And two enrichments – with a better/worse atrazine-degrading efficiency (ATB/ATW) – were derived from the original enrichment AT by continuous sub-enrichment with or without atrazine. Subsequently, an Arthrobacter sp. strain, AT5, that was capable of degrading atrazine was isolated from enrichment AT. The bacterial community structures of these three enrichments were investigated using high-throughput sequencing analysis of the 16S rRNA gene. The atrazine-degrading efficiency improved as the abundance of Arthrobacter species increased in enrichment ATB. The relative abundance of Arthrobacter was positively correlated with those of Hyphomicrobium and Methylophilus, which enhanced atrazine degradation via promoting the growth of Arthrobacter. Furthermore, six genera/families such as Azospirillum and Halomonas showed a significantly negative correlation with atrazine-degrading efficiency, as they suppressed atrazine degradation directly. These results suggested that atrazine-degrading efficiency was affected by not only the degrader but also some non-degraders in the community. The promotion and suppression of atrazine degradation by Methylophilus and Azospirillum/Halomonas, respectively, were experimentally validated in vitro, showing that shifts in both the composition and abundance in consortia can drive the change in the efficiency of catabolic function. This study provides valuable information for designing enhanced bioremediation strategies.